Janus Magnetic Nanoplatform for Magnetically Targeted and Protein/Hyperthermia Combination Therapies of Breast Cancer - Zuo, Shuting; Wang, Jing; An, Xianquan; Zhang, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
Protein therapeutics have been considered a promising strategy for cancer treatment due to their highly specific bioactivity and few side effects. Unfortunately, the low physiological stability and poor membrane permeability of most protein drugs greatly limit their clinical application. Furthermore, single-modality protein therapeutics show insufficient efficacy. To address these issues, Janus magnetic mesoporous silica nanoparticles (Janus MSNNPs) were developed to preload ribonuclease A (RNaseA) to simultaneously realize the magnetically enhanced delivery of protein drugs and magnetic hyperthermia-enhanced protein therapy. Janus MSNNPs showed a high RNaseA loading ability and pH-responsive drug release behavior. Furthermore, an external magnetic field could remarkably enhance the therapeutic effect of RNaseA-loaded Janus MSNNPs due to the improved intracellular internalization of RNaseA. Importantly, Janus MSNNPs possessed an outstanding magnetic hyperthermia conversion efficiency, which could generate hyperthermia under an alternating magnetic field, effectively supplementing protein therapy by a combined effect. In vitro and in vivo experiments confirmed the high anticancer outcome and low side effects of this intriguing strategy for breast cancer based on Janus MSNNPs. Hence, Janus MSNNPs might be an effective and safe nanoplatform for magnetically combined protein therapy.